Protease-Activation of Fc-Masked Therapeutic Antibodies to Alleviate Off-Tumor Cytotoxicity - Elter, Adrian; Yanakieva, Desislava; Fiebig, David; Hallstein, Kerstin; Becker, Stefan; Betz, Ulrich; Kolmar, Harald (Frontiers in Immunology, 2021)
The interaction of the Fc region of therapeutic antibodies and antibody-drug conjugates with Fcγ receptors (FcγRs) can lead to unpredictable and severe side effects. Over the last decades several strategies have been developed to overcome this drawback, including extensive Fc- and glycoengineering and antibody isotype switching. However, these approaches result in permanently Fc-silenced antibody derivates which partially or completely lack antibody-mediated effector functions. Nevertheless, for a majority of antibody-based drugs, Fc-mediated effector functions, like antibody-dependent cell-mediated cytotoxicity (ADCC), antibody-dependent cell-mediated phagocytosis (ADCP) as well as complement-dependent cytotoxicity (CDC), represent the most substantial modes of action. We argued that a new strategy combining the beneficial properties of Fc-silencing and controlled activation of effector functions can pave the way to potent antibody therapeutics, reducing the FcγRs-mediated off-target toxicity. We present a novel Fc-tamed antibody format, where the FcγR-binding sites of antibodies are blocked by anti-isotypic masking units, hindering the association of FcγR and complement component 1 (c1q) to the Fc domain. The masking units were genetically fused to trastuzumab, including a protease-addressable peptide-liker. Our Fc-tamed antibodies demonstrated completely abolished interaction to soluble high-affinity Fcγ-Receptor I and c1q. In reporter cell-based ADCC assays, our Fc-tamed antibodies exhibited a 2,700 to 7,100-fold reduction in activation, compared to trastuzumab. Upon demasking by a tumor-associated protease, the Fc-activated antibodies demonstrated restored FcγR-binding, c1q-binding and the ability to induce potent ADCC activation. Furthermore, cell killing assays using donor-derived NK cells were performed to validate the functionality of the Fc-tamed antibody variants. To our knowledge, this approach represents the first non-permanently Fc-silenced antibody, which can be re-activated by a tumor-associated protease, eventually extending the field of novel antibody formats.